Case report: JAK inhibitor treatment of immune dysregulation symptoms in a patient with PTPN2 deficiency - Roppelt, Anna; Markina, Ulyana; Beloglazova, Irina; Parshin, Vasily; Kanner, Dmitry; Pershin, Dmitry; Fadeeva, Mariia; Raykina, Elena; Aleksenko, Maxim; Karaulov, Alexander; Lysenko, Mariana; Fomina, Daria (Frontiers in Immunology, 2025)
A heterozygous mutation in the PTPN2 gene has recently been described in several patients exhibiting symptoms of immune dysregulation. The gene encodes a ubiquitous non-receptor T-cell protein tyrosine phosphatase that exerts a negative feedback on the JAK–STAT pathway. Limited clinical data are available advocating the use of JAK inhibitors as an effective treatment for autoimmune complications of PTPN2 deficiency. However, the mechanism of pathogenesis for these complications suggests this possibility. We report on a 32-year-old male patient with interstitial lung disease, cytopenia, and lymphadenopathy accompanied by de-novo deletion in PTPN2. The patient has been receiving systemic steroid treatment for decades, which has resulted in hormone dependence as well as therapy-related adverse side effects. After the diagnosis of PTPN2 deficiency, treatment with the JAK inhibitor ruxolitinib was initiated at a dose of 15 mg per day, which was escalated to 30 mg daily after 1 month. The steroid treatment was discontinued within 3 months. At the 9- and 16-month checkpoint, after 6 and 13 months correspondingly of monotherapy with ruxolitinib at a dosage of 30 mg per day, the patient had stable blood counts, lymphadenopathy decreased, and the lung interstitial disease improved. Thus, according to our experience, JAK inhibitors are able to alleviate the PTPN2 deficiency symptoms, including hematological changes and interstitial lung damage.